2018
DOI: 10.1007/s11166-018-9271-9
|View full text |Cite
|
Sign up to set email alerts
|

Goals as reference points in marathon running: A novel test of reference dependence

Abstract: In a large-scale field study of marathon runners, we test whether goals act as reference points in shaping the valuation of outcomes. Theories of reference-dependent preferences, such as Prospect Theory, imply that outcomes that are just below or just above a reference point are evaluated differently. Consistent with the Prospect Theory value function, we find that satisfaction as a function of relative performance (the difference between a runner's finishing time goal and her actual finishing time) exhibits l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 108 publications
3
35
0
Order By: Relevance
“…First, multiple goals can occur on a single variable. Markle et al (2018) demonstrated how satisfaction for running times was influenced by multiple time goals, including best finish times, personal goals, and most recent finishes. In another example, corporate investment decisions of managers were influenced by the company's current performance and its target performance (Sullivan and Kida 1995).…”
Section: Happiness and Multiple Reference Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, multiple goals can occur on a single variable. Markle et al (2018) demonstrated how satisfaction for running times was influenced by multiple time goals, including best finish times, personal goals, and most recent finishes. In another example, corporate investment decisions of managers were influenced by the company's current performance and its target performance (Sullivan and Kida 1995).…”
Section: Happiness and Multiple Reference Pointsmentioning
confidence: 99%
“…Goals function as reference points in a manner consistent with prospect theory's value function (Heath et al 1999). For example, Markle et al (2018) asked marathon runners to forecast or report their satisfaction with exceeding or falling short of their goals for a race. Predicted and actual satisfaction were both consistent with loss aversion and diminishing sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…In a series of laboratory studies, Heath et al (1999) proposed that the goal can be used as a reference point, proving that the characteristics of the value function of the prospect theory can explain the effort and satisfaction of the goal reference point in completing the task, and also found the support of diminishing sensitivity, which means that changes closer to the goal have a greater impact than changes farther from the goal. In a large-scale field study of marathon runners, Markle et al (2018) found that the goal was to serve as a reference point to form the final utility of the contestants. They asked marathon runners to predict or report their satisfaction with the goals above or below the competition.…”
Section: Single Reference Pointmentioning
confidence: 99%
“…The first is to set multiple goals in a variable. For example,Markle et al (2018) proved the effect of multiple goals on running time satisfaction, including optimal completion Y. Y. Su, L. Y. Xiong time, personal goals, and recent completion.…”
mentioning
confidence: 99%
“…In addition to the economic theory literature, there is an increasing number of empirical studies investigating the effects of goal setting on performance in the laboratory and in the field. See for instance Brookins et al (2017), Corgnet et al (2015Corgnet et al ( , 2018, Dalton et al (2016), Koch and Nafziger (2017), Markle et al (2018), and Uetake and Yang (2018), and for experimental studies about goal setting with university students, see e.g., Clark et al (2018), Dobronyi et al (2017), andVan Lent andSouverijn (2017). In Van Lent and Souverijn (2017) goals are set during one-on-one interviews between students and their randomly assigned mentor.…”
Section: Introductionmentioning
confidence: 99%